2011
DOI: 10.1175/2010jtecha1488.1
|View full text |Cite
|
Sign up to set email alerts
|

A New Dual-Polarization Radar Rainfall Algorithm: Application in Colorado Precipitation Events

Abstract: The efficacy of dual-polarization radar for quantitative precipitation estimation (QPE) has been demonstrated in a number of previous studies. Specifically, rainfall retrievals using combinations of reflectivity (Z h ), differential reflectivity (Z dr ), and specific differential phase (K dp ) have advantages over traditional Z-R methods because more information about the drop size distribution (DSD) and hydrometeor type are available. In addition, dual-polarization-based rain-rate estimators can better accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
108
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(119 citation statements)
references
References 36 publications
(38 reference statements)
2
108
0
9
Order By: Relevance
“…The lowest NSE values were, typically, closest to each of the radars (between 0.4 and 0.8), with the notable exception of the closest gauge to KSGF. In general, the RREC performed worst at the largest of ranges, potentially due to the algorithm's ability to incorrectly assess the hydrometeors present (Cifelli et al, 2010;Yang et al, 2016). Additionally, the poor performance by the R(DSMZ)-tropical equation is due to the lack of tropical precipitation within central Missouri.…”
Section: Overall Algorithm Performancementioning
confidence: 99%
“…The lowest NSE values were, typically, closest to each of the radars (between 0.4 and 0.8), with the notable exception of the closest gauge to KSGF. In general, the RREC performed worst at the largest of ranges, potentially due to the algorithm's ability to incorrectly assess the hydrometeors present (Cifelli et al, 2010;Yang et al, 2016). Additionally, the poor performance by the R(DSMZ)-tropical equation is due to the lack of tropical precipitation within central Missouri.…”
Section: Overall Algorithm Performancementioning
confidence: 99%
“…15 Algorithm R2 was developed over 22 summer storm events by WRC (2014) as mentioned in Step 1. Algorithm R3 is the CSU-ICE algorithm (Cifelli et al, 2011). Algorithm R3 itself consists of four different algorithms, R(Z), R(Z, Z DR ), R(K DP , Z DR ), and R(K DP ) for the given ranges of the three polarimetric variables.…”
Section: Steps 4 and 5: 10mentioning
confidence: 99%
“…Ryzhkov and Zrnić (1995a) found that algorithms using Z DR and K DP were better than other algorithms. The Colorado State University (CSU) ICE algorithm and Joint POLarization Experiment (JPOLE) algorithm are synthesized methods that selectively use Z, Z DR , and K DP with respect to the range of polarimetric variables or rain rate (Ryzhkov et al, 2003;Cifelli et al, 2011). 15…”
Section: Introduction 20mentioning
confidence: 99%
“…In particular, dual-polarization radar that provides information on the reflectivity (Z H ), differential reflectivity (Z DR ), differential phase ( DP ), specific differential phase (K DP ), and cross-correlation coefficient (ρ hv ) can distinguish precipitation types by means of backscatter and the differential propagation phase of hydrometeors. Dual-polarization radar can also be used to obtain more information about the raindrop size distribution (DSD), and this in turn can help to reduce the impact of DSD variability on rainfall estimations (Cifelli et al, 2011). The DSD can be characterized by parameters such as the diameter, concentration, orientation, and shape.…”
Section: Introductionmentioning
confidence: 99%